2003
DOI: 10.1176/appi.ajp.160.11.2057
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Complex Sounds: Abnormal Pattern of Cortical Activation in Autism

Abstract: These findings suggest that abnormal auditory cortical processing is implicated in the language impairments and the inadequate response to sounds typically seen in autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
118
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(134 citation statements)
references
References 15 publications
13
118
2
1
Order By: Relevance
“…An impairment of this region also could contribute to the language difficulties and consequent communication problems of autistic subjects. 31 GM loss in our ASD patients involved the precuneus that is connected with multiple areas of the interhemispheric cortex, convexity, basal ganglia, and thalami. 32 Changes occurring in this pivotal area are consistent with recent claims that autism is a connectivity disorder.…”
Section: Figmentioning
confidence: 84%
“…An impairment of this region also could contribute to the language difficulties and consequent communication problems of autistic subjects. 31 GM loss in our ASD patients involved the precuneus that is connected with multiple areas of the interhemispheric cortex, convexity, basal ganglia, and thalami. 32 Changes occurring in this pivotal area are consistent with recent claims that autism is a connectivity disorder.…”
Section: Figmentioning
confidence: 84%
“…In this regard, a number of electrophysiological and neuroimaging studies reported right hemisphere dominance of auditory processing and speech perception in individuals with ASD, while controls showed left hemisphere dominance (e.g., Boddaert et al 2003;Bruneau et al 1999;Eyler et al 2012;Flagg et al 2005;Müller et al 1998Müller et al , 1999Redcay and Courchesne 2008;Roberts et al 2008; but see Whitehouse and Bishop 2008). Flagg et al (2005), in particular, observed a reversed maturational pattern of lateralization: Whereas controls matured from bilateral activation to left hemisphere dominance in the processing of speech sounds, children with autism matured towards right hemisphere dominance.…”
Section: Introductionmentioning
confidence: 99%
“…Structural and functional neuroimaging studies of language areas have provided evidence that differences in lateralization may underlie language and communication difficulties in individuals with ASD (Bigler et al, 2007;Boddaert et al, 2003;Chandana et al, 2005;Chiron et al, 1995;Flagg et al, 2005;Herbert et al, 2002;. For example, a series of volumetric studies by Herbert and colleagues (Herbert et al, 2002;, demonstrated that brain asymmetry patterns differed in children with high functioning autism compared to controls.…”
Section: Introductionmentioning
confidence: 99%